2021
DOI: 10.1002/brb3.2178
|View full text |Cite
|
Sign up to set email alerts
|

Global efficiency of the motor network is decreased in Parkinson's disease in comparison with essential tremor and healthy controls

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…The global efficiency represents the information efficiency of networks at the global level. The reduced global efficiency of functional network has been reported in PD patients 90,91 were consistent with the findings reported by previous studies showing that nodal topology of caudate in functional network were significantly altered in PD [92][93][94][95] . The reduction of local information efficiency in caudate of T-carriers indicated that BIN3 rs2280104 T allele is harmful in PD, which was consistent with previous study showing that BIN3 rs2280104 T allele was associated with increased risk of PD.…”
Section: The Effects Of Bin3 Rs2280104 T Allele On Functional Networksupporting
confidence: 92%
“…The global efficiency represents the information efficiency of networks at the global level. The reduced global efficiency of functional network has been reported in PD patients 90,91 were consistent with the findings reported by previous studies showing that nodal topology of caudate in functional network were significantly altered in PD [92][93][94][95] . The reduction of local information efficiency in caudate of T-carriers indicated that BIN3 rs2280104 T allele is harmful in PD, which was consistent with previous study showing that BIN3 rs2280104 T allele was associated with increased risk of PD.…”
Section: The Effects Of Bin3 Rs2280104 T Allele On Functional Networksupporting
confidence: 92%
“…To fill the current research gap, we used probabilistic tractography in this study, which is capable of resolving the problem of crossing fibers in white matter voxels, 19 to characterize the brain organization of the motor network in SCA3/MJD. Motor networks have been studied in other neurodegenerative diseases comprising the precentral cortex, basal ganglia, thalamus, ventral diencephalon, and cerebellum 17,20–23 . We used network‐based statistics (NBS), 24 a statistical approach that identifies connections in a graph that may be relevant to diagnostic status, 25 to find different subnetworks in preclinical and ataxic SCA3/MJD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Motor networks have been studied in other neurodegenerative diseases comprising the precentral cortex, basal ganglia, thalamus, ventral diencephalon, and cerebellum. 17 , 20 , 21 , 22 , 23 We used network‐based statistics (NBS), 24 a statistical approach that identifies connections in a graph that may be relevant to diagnostic status, 25 to find different subnetworks in preclinical and ataxic SCA3/MJD patients. Given that previous imaging studies have shown that morphological changes already occur in the cerebellum at the preataxic stage, we hypothesized that motor network abnormalities are already detectible before the onset of ataxia, and motor network alterations are associated with disease severity in SCA3/MJD.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that brain structural and functional connections are damaged in the early stages of PD. A previous rs-fMRI study of 54 PD patients found that the global efficiency of the motor network was decreased in PD patients compared with tremor patients and HCs (Novaes et al, 2021). Another rs-fMRI study showed that the global and local efficiency of the sensorimotor network and the visual network were disrupted in PD (Fang et al, 2017).…”
Section: Discussionmentioning
confidence: 96%